Sistem E-SCM untuk Manajemen Suplai Barang Produksi Pecah Belah berbasis Web - Cindy Ramadhani; Hambali Hambali; Akmal Akmal (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
E-SCM is a system that can manage the delivery of goods that can be integrated between consumers, suppliers and traders. The purpose of this research is to create a web-based E-SCM system for glassware inventory management, which will be implemented at the Glosir Raju store. The model used to build this system is the system development life cycle, which includes the analysis, design, implementation, and testing phases. Data collection techniques were carried out by interview and observation. While the design phase in this research consists of making interfaces, use case diagrams, and class diagrams. Our result is a web-based E-SCM system for managing the distribution of glassware. The test results show that all functions work well in this system and follow the set design. Therefore, the E-SCM system for glassware shops makes the delivery of raw materials faster, and there are no delays in delivery, making the production process faster, more effective, and efficient, especially at the Glosir Raju store.